-4y+11=17-3y

Simple and best practice solution for -4y+11=17-3y equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4y+11=17-3y equation:


Simplifying
-4y + 11 = 17 + -3y

Reorder the terms:
11 + -4y = 17 + -3y

Solving
11 + -4y = 17 + -3y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '3y' to each side of the equation.
11 + -4y + 3y = 17 + -3y + 3y

Combine like terms: -4y + 3y = -1y
11 + -1y = 17 + -3y + 3y

Combine like terms: -3y + 3y = 0
11 + -1y = 17 + 0
11 + -1y = 17

Add '-11' to each side of the equation.
11 + -11 + -1y = 17 + -11

Combine like terms: 11 + -11 = 0
0 + -1y = 17 + -11
-1y = 17 + -11

Combine like terms: 17 + -11 = 6
-1y = 6

Divide each side by '-1'.
y = -6

Simplifying
y = -6

See similar equations:

| 15b/2a | | 2w+4x+15y+6w+11x+7y= | | 4ab/5b^4 | | x^2=0.0016 | | 3+3.2p=5.56 | | 1*(-4+(-8))= | | 3.2p=5.56 | | 7/x=2 | | X^2=4900 | | 30=5(x+11) | | 4.3-1.95x=4.4-1.98x | | x/7=0.02 | | g(x)=-2x^2-3 | | 123=7 | | (4x-8)+2=12 | | 30/8=90/m | | 3s-21=-12+2s | | 7y-2=-56+y | | 75n+100=5509 | | x/7=0.18 | | 5/3s=10 | | -5/9m=-20 | | -5/7r=-20 | | -30p=-300 | | 2x-3=.5x-6 | | x*2=20 | | t-48=44 | | x*11=18 | | y=5x^2-5x+10 | | (10uv^3-8v^6x^5)/4v^6 | | 13=5y-2y-2 | | 1x-12=1 |

Equations solver categories